High-rate quantum key distribution with compact state preparation and detection - Guan-Jie Fan-Yuan; Wei-Xin Xie; De-Yong He; Xiao-Juan Huang; Shuang Wang; Zhen-Qiang Yin; Wei Chen; Qiong Li; Hao-Kun Mao; Guo-Wei Zhang; Yu-Long Wang; Guang-Can Guo; et al. (Proceedings of the National Academy of Sciences, 2026)
Quantum key distribution (QKD) is a promising technology for information-theoretic secure communications. The practicality of QKD systems is critical for large-scale network deployment, requiring both high key generation rate and miniaturized modules for quantum-state preparation and detection. Here, we report a deployable QKD system that achieves secure key rates of 60.33 ± 0.03 Mbps at 10 km and 3.08 ± 0.20 Mbps at 100 km. The system integrates a dual-parallel Mach–Zehnder encoder to achieve high-fidelity, unified preparation of polarization and decoy states via single-step modulation in a compact design. Meanwhile, we developed miniaturized single-photon avalanche detectors operating at 2.5 GHz, achieving high count rates while maintaining low noise. This high-performance and compact solution establishes a feasible roadmap for urban secure communication networks that require high capacity and bandwidth.